The changing molecular epidemiology of Enterococcus faecium harbouring the van operon at a teaching hospital in Western Australia: A fifteen-year retrospective study - Terence Lee; Stanley Pang; Denise A. Daley; Julie C. Pearson; Sam Abraham; Geoffrey W. Coombs (Elsevier, 2022)
Introduction: Enterococcus faecium is an opportunistic pathogen that has become one of the leading causes of hospital acquired infection that are resistant to multiple critically important antimicrobials. Aim: The objective of the study was to describe the molecular characteristics and relationship between major strains of E. faecium harbouring the van operon and to determine if the strains had increasing virulence and antimicrobial resistance determinants over time. Methods: E. faecium harbouring the van operon detected using PCR from surveillance rectal swabs of patients that were admitted to high-risk units at a Perth teaching hospital from 2001 to 2015 were retrospectively analysed using a whole genome sequencing and bioinformatics approach. Results: ST18, ST78, ST80, ST173, ST203 and ST555 were identified as the major STs accounting for 93.7% of E. faecium isolates. Except for ST173, major STs identified at Royal Perth Hospital (RPH) have been reported across Australia and internationally. Isolates from each ST formed independently branched phylogenetic clusters with each harbouring unique virulence and antimicrobial resistance profiles. Depending on the ST, different genes conferring resistance to similar antimicrobial classes were identified. Except for ST80 which harboured the vanA type operon, all major strains harboured the vanB operon conferring only vancomycin resistance. Conclusion: Major strains of E. faecium isolated over 15-years showed unique virulome and resistome profiles with no indication of increasing virulence or antimicrobial resistance determinants. Strains were distantly related and the acquisition of different genes encoding similar antimicrobial resistances suggest the independent evolution of each strain. Data Summary: The whole genome sequences of all isolates from this study are accessible from the NCBI-SRA database under project number PRJNA575940 and PRJNA524213. Published reference sequence Aus0004 was obtained from NCBI-SRA under project number PRJNA86649 DOI:10.1128/JB.00259-12